Event-Driven Changes in Return Connectedness Among Cryptocurrencies - Peter Albrecht; Evžen Kočenda (CESifo GmbH, 2025)
Our study presents an in-depth analysis of the interconnectedness in returns among five major cryptocurrencies from 2018 to 2023. Our work introduces novel findings by employing a novel bootstrap-after-bootstrap method of Greenwood-Nimmo et al. (2024) to establish a link between increases in connectedness and various systematic events. We found a clear rise in connectedness within a month following the event for ten endogenously selected events. Further, we identify Bitcoin and Ethereum as net return transmitters, mainly to Binance coin and Ripple. Moreover, we found that these transmissions increased by up to 20% for up to one month after the shocks occurred. We calculate optimal portfolio weights and hedging ratios for cryptocurrency risk management. Our findings reveal that Cardano and Ripple are the most effective choices in portfolio optimization. The implications of this study are significant for devising strategies in portfolio management and risk hedging, offering valuable guidance for policy formulation in the financial sector.
Keywords: H56; G11; G15; Q40; 330; return connectedness; cryptocurrencies; bootstrap-after-bootstrap procedure; portfolio composition and hedging